Peritonitis in peritoneal dialysis patients in Japan: a 2013 retrospective questionnaire survey of Japanese Society for Peritoneal Dialysis member institutions. Issue 1 (December 2016) - Higuchi, Chieko; Ito, Minoru; Masakane, Ikuto; Sakura, Hiroshi
Abstract Background Peritonitis is the main cause of withdrawal from peritoneal dialysis (PD) therapy in Japan. The precise extent of PD-associated peritonitis in Japan has not been investigated since 2005; we aimed to clarify the recent incidence and prognosis of PD peritonitis. Methods The 248 institutional members of the Japanese Society for Peritoneal Dialysis were surveyed by questionnaire regarding peritonitis episodes during January 1 to December 31, 2013. Results Replies from 114 members were received regarding 3042 PD patients, including 516 peritonitis patients, covering a total observation period of 31, 686 patient months. The incidence of peritonitis in this study was 0.195 episodes per year. Detailed data on 544 peritonitis episodes in 466 patients was obtained. The causes, in ranked order, were unknown reason, contamination at peritoneal fluid exchange, and extension of intra-abdominal cavity infection. Effluent culture methods included using a blood culture bottle (50.9 %), large-volume culture (culturing sediment after centrifuging effluent) (31.7 %), and direct culture of effluent using a culture dish (12.7 %). The rank order of microbes identified in peritoneal effluent cultures was culture-negative, Streptococcus sp. andStaphylococcus aureus . Empiric therapy with two kinds of antibiotics was administered to 406 cases (75.2 %), most commonly cefazolin + ceftazidime. Antibiotic administration methods included intraperitoneal (51.4 %), intravenous (46.4 %), and oral (2.2 %). After a peritonitis episode, 461 patients (84.7 %) continued PD therapy, 80 (14.7 %) withdrew from PD treatment, and 6 (1.1 %) died. Prognosis among patients grouped by antibiotic administration method was statistically significantly different; in the oral administration group, the rates of mortality and catheter replacement were higher. Logistic regression analysis showed that catheter exit-site infection and frequency of past peritonitis episodes were independent factors associated with PD treatment withdrawal. Conclusions Although the overall incidence of PD peritonitis in Japan was relatively low, several areas for future improvement were identified: unknown reason and culture-negative were the most frequently cited causes of peritonitis; 1.1 % of patients died, and 13.6 % discontinued PD therapy. Improvements in effluent culture techniques, antibiotic administration methods, etiology determination, and patient education could help. A more effective protocol must be established to further improve the treatment of PD peritonitis in Japan.